Batuques, folias e ladainhas: A cultura do Quilombo do CRIA-Ú em Macapá e sua educação - Videira, Piedade Lino (2010)
The education in Quilombos (hiding-places of fugitive black people slaves) must consider ethnic, historical, anthropological and cultural aspects from this tangible and intangible natural national heritage. These aspects are manifested in the context of the CRIA-Ú Quilombo, territory with mysterious features of African descent because of the mythic power that circulate there, with a lot of African things. Based on this assumption the main objective of this study is focused on analyzing and understanding the culture constituted and experienced by the CRIA-Ú community in specific dances like Batuque and Marabaixo as elements of redefinition of educational practice and curriculum aimed at valuing African (Brazilian)history and culture according to the appointment of Law 10.639/03. With this purpose I have adopted as a methodological perspective the participant observation and intervention research, both developed in the CRIA-Ú Quilombo territory and at the Public State School José Bonifácio, situated in the geographical area of the CRIA-Ú Quilombo. The period of the fieldwork took place between the years 2007-2009. Meanwhile the participant observation consisted of daily monitoring by the quilombola (black people slaves who took refuge in a Quilombo) community, mediated by interviews with historical beings, inhabitants of the Quilombo with over 40 years of age. The intervention research stemmed from the analysis of material collected in participant observation, as well as on an exploratory study conducted in the context of the school. The analysis of the development of systematic information on the treatment of research data, combined with the theoretical framework established by writers such as ANGELS, 2009; Cunha Jr., 2001, 2009; BIRTH, 2007; RAFFESTIN, 1993; SANTOS, 2002) who contributed to problem-solving dialogue with the categories: Afro descent, territory, black memories and Quilombos. The results showed that this course of Batuque from CRIA-Ú Quilombo is not just for bringing people together to celebrate their saints and spiritual entities, but rather to reaffirm the knowledge they have achieved their heirs of their ancestors as a strategy for survival and maintenance of its history and culture. The thesis deals with various aspects of lives from people who live in CRIA-Ú, without claiming to exhaust them. The paper focuses on the argument that local culture is in fundamental educational content to partake of their self-worth, serving as a rich educational courseware.